Abdominotransanal approach to pouch colon associated with rectal atresia - Kazez, Ahmet; Ozel, S. Kerem; Bakal, Una; Sarac, Mehmet (W B Saunders Co-Elsevier Inc, 2009)
Pouch colon anomaly and high anorectal malformation are well-defined rare anomalies. The association of pouch colon anomaly with rectal atresia has previously been defined in only one case. In this study, a 2-day-old baby is presented with pouch colon anomaly without fistula and with rectal atresia. As a second case in the literature, this pathologic condition has been treated through the abdominotransanal route by using a single-stage endorectal coloanal pull-through. Being uncommon and having an important therapeutic approach, this case has been evaluated as worth presenting. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Pouch colon; Rectal atresia; Treatment